Sistema Para Enriquecimiento De Biogás Mediante Biomasa Microalgal (2023)
This degree project focuses on the development of an innovative system that combines a biodigester and a photobioreactor with the purpose of enhancing methane production while effectively removing carbon dioxide (2). Methane is a valuable gas as an energy source, and the elimination of 2 significantly contributes to mitigating climate change